Studi Tentang Pengetahuan, Sikap dan Tindakan Vulva Hygiene Remaja dengan Kejadian Keputihan pada Siswi SMA Negeri 1 Kota Kendari - Amiruddin, Amiruddin; Darlian, Lili; Safitri, Indra (bionature, 2021)
Abstract. Vaginal discharge is a problem that is often experienced by young women, especially in the transition period along with the maturity of the reproductive organs that need special attention. This study aims to determine the relationship between the level of knowledge, attitudes and actions of adolescent vulva hygiene with the incidence of vaginal discharge in students of SMA Negeri 1 Kendari. This type of research is associative with a proportional stratified random sampling design. The population of this study were students of SMA Negeri 1 Kendari who experienced vaginal discharge as many as 322 people. The results showed that from 126 respondents there were 64 (50.80%) respondents in the high knowledge category and 62 (49.2%) respondents in the medium knowledge category, for attitudes there were 100 (79.37%) respondents in the good attitude category and 26 (20 ,63%) respondents have a moderate attitude category, and vulvar hygiene measures there are 90 (71.43%) respondents have a good vulvar hygiene action category and 36 (28.57%) respondents have a bad vulvar hygiene action category. Based on the results of the chi-square test, it can be concluded that the level of knowledge, attitudes and actions of vulva hygiene is related to the incidence of vaginal discharge in students of SMA Negeri 1 Kendari (P 0.05).Keywords: knowledge, attitude, vulvar hygiene action, adolescent vaginal discharge